2014
DOI: 10.1590/s0036-46652014000500011
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis-Related Knowledge Among Pregnant and Postpartum Women Attended in Public Health Units in Niterói, Rio De Janeiro, Brazil

Abstract: The present study conducted a toxoplasmosis-related knowledge level survey with 400 pregnant and puerperal women attended in public health units in the municipality of Niterói, Rio de Janeiro. Only 111 (27.8%) women claimed to know about the disease. Most of them (n = 289; 72.2%) had never heard about toxoplasmosis nor knew how to prevent the infection by Toxoplasma gondii. A significant difference (p = 0.013) regarding the presence of anti-T. gondii IgG was observed between women who claimed to know about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
1
15
1
4
Order By: Relevance
“…A survey of pregnant and postpartum women in Brazil showed that only 27.8% knew that the disease existed. Most of them (72.2%) had never heard of toxoplasmosis [31]. In a study from Zimbabwe, only 4% of 49 respondents knew that toxoplasmosis was a zoonosis that could be transmitted via cats [32].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of pregnant and postpartum women in Brazil showed that only 27.8% knew that the disease existed. Most of them (72.2%) had never heard of toxoplasmosis [31]. In a study from Zimbabwe, only 4% of 49 respondents knew that toxoplasmosis was a zoonosis that could be transmitted via cats [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the importance of primary prevention [16][17][18][19][20][21], early diagnosis and treatment, and case notification, should be emphasized, so as to prevent or attenuate fetal infection [22]. The supply of educational material with information about the prevention of T. gondii infection has been effective in reducing seroconversion rates [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Conforme a tabela 2, a maioria das gestantes desconhecia às formas de transmissão (51,4%), complicações (72,9%), meios de diagnóstico (57,1%), profilaxia e tratamento (74,3%) e as medidas preventivas (52,9%) da toxoplasmose. Da mesma maneira, Millar et al (2014) ao realizarem um levantamento do conhecimento de 400 gestantes e puérperas atendidas na rede pública de saúde do município de Niterói -RJ sobre a toxoplasmose verificaram que 72,2% das participantes nunca tinham ouvido falar sobre a toxoplasmose, principalmente sobre as formas de prevenção da infecção pelo T. gondii.…”
Section: Methodsunclassified